Gambaran Pola Kebiasaan Sarapan dan Jajan di Cofee Break Sekolah Pada Anak Gizi Lebih Di Sdit Al-Hikmah Maros - Nur Azizah; Djunaidi Dachlan; Sabaria Manti Battung; Aminuddin Syam; Marini Amalia Mansur (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2021)
Introduction: Children of primary school age are prone to nutritional problems, one ofwhich is over nutrition. Globally, the prevalence of over nutrition children increased byaround 47.1%, while in Indonesia it increased to 10.8% and 9.2%. The main cause of overnutrition in children is the wrong diet which is influenced by the family and schoolenvironment. Family plays a role in forming healthy eating behavior, one of which is to getbreakfast habits. The school also plays a role in providing healthy food for children whilethey are at school. Purpose: To know the description of breakfast habits and snack habits atschool coffee breaks in children with over nutrition at SDIT Al-Hikmah Maros. Materialsand Methods: Descriptive research design. The sample was students in grades 4-6 who had